ANALISIS KINERJA KEUANGAN PT.VALE INDONESIA,Tbk SEBELUM DAN SESUDAH DIVESTASI - Aris Sarangnga'; Marinus Ronal; Elisabet Pali (ITB AAS Indonesia Surakarta, 2025)
“Financial Performance Analysis of PT Vale Indonesia, Tbk Before and After Divestment”The purpose of this study is to analyze the financial performance of PT Vale Indonesia, Tbk before and after divestment. This research employs Profitability Ratios and Liquidity Ratios to measure financial performance, including Net Profit Margin (NPM), Return on Assets (ROA), Current Ratio, and Quick Ratio.The data collection techniques used in this study include Library Research and Field Research, in the form of documentation by downloading PT Vale Indonesia, Tbk's financial statements. Based on the analysis, the financial performance of PT Vale Indonesia, Tbk before and after divestment showed significant changes. Profitability after divestment (2021-2023) became more stable and higher, with NPM averaging above 70%, indicating that the company became more efficient in generating profit from revenue. ROA consistently increased from 6.78% in 2021 to 9.37% in 2023, demonstrating that the company optimized its asset utilization to generate profit after divestment. This indicates that after divestment, the company was able to improve operational efficiency and focus on a more profitable core business. Divestment had a positive impact on the company's profitability, as both NPM and ROA became more stable and showed improvements, reflecting greater efficiency in operational and asset management. Meanwhile, liquidity also became stronger and more stable. Before divestment, the Current Ratio dropped significantly to 51.7% in 2019, indicating potential liquidity difficulties. After divestment, the Current Ratio drastically increased to 495%-565%, showing that the company had a significantly higher amount of current assets compared to its short-term liabilities. Keywords: Divestment, Net Profit Margin, Return on Assets, Current Ratio, Quick Ratio.